Intracellular Nitrate of Marine Diatoms as a Driver of Anaerobic Nitrogen Cycling in Sinking Aggregates - Kamp, Anja; Stief, Peter; Bristow, Laura A.; Thamdrup, Bo; Glud, Ronnie N. (Frontiers in Microbiology, 2016)
Diatom-bacteria aggregates are key for the vertical transport of organic carbon in the ocean. Sinking aggregates also represent pelagic microniches with intensified microbial activity, oxygen depletion in the center, and anaerobic nitrogen cycling. Since some of the aggregate-forming diatom species store nitrate intracellularly, we explored the fate of intracellular nitrate and its availability for microbial metabolism within anoxic diatom-bacteria aggregates. The ubiquitous nitrate-storing diatom Skeletonema marinoi was studied as both axenic cultures and laboratory-produced diatom-bacteria aggregates. Stable 15N isotope incubations under dark and anoxic conditions revealed that axenic S. marinoi is able to reduce intracellular nitrate to ammonium that is immediately excreted by the cells. When exposed to a light:dark cycle and oxic conditions, S. marinoi stored nitrate intracellularly in concentrations > 60 mmol L-1 both as free-living cells and associated to aggregates. Intracellular nitrate concentrations exceeded extracellular concentrations by three orders of magnitude. Intracellular nitrate was used up within 2-3 days after shifting diatom-bacteria aggregates to dark and anoxic conditions. Thirty-one percent of the diatom-derived nitrate was converted to nitrogen gas, indicating that a substantial fraction of the intracellular nitrate pool of S. marinoi becomes available to the aggregate-associated bacterial community. Only 5% of the intracellular nitrate was reduced to ammonium, while 59% was recovered as nitrite. Hence, aggregate-associated diatoms accumulate nitrate from the surrounding water and sustain complex nitrogen transformations, including loss of fixed nitrogen, in anoxic, pelagic microniches. Additionally, it may be expected that intracellular nitrate not converted before the aggregates have settled onto the seafloor could fuel benthic nitrogen transformations.